2020
DOI: 10.2147/cmar.s271165
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of miR-515-5p on Proliferation and Drug Sensitivity of Retinoblastoma Cells</p>

Abstract: Background: Retinoblastoma (RB) is a common malignancy in children eyes. Aberrant microRNA (miR) expression is observed in many cancer cases. miR-515-5p is reported to be concerned with the course of many cancers. This study explores the role of miR-515-5p in proliferation and drug sensitivity of RB cells. Methods: Human RB cell lines (WERI-RB1, SO-RB50 and Y79) and human retinal pigment epithelial cell line ARPE-19 were utilized in this study. Drug-resistant cells SO-RB50/VCR and SO-RB50/CBP were constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…And overexpression of miR‐515‐5p inhibited the proliferation, invasion, and metastasis of liver cancer cells by regulating the IL‐6/JAK/STAT3 signaling pathway (Ni et al, 2020). However, Yuan indicated that miR‐515‐5p overexpression could inhibit the proliferation and drug resistance of retinoblastoma cells by targeted downregulation of Notch1 expression (Yuan et al, 2020). Moreover, miR‐515‐3p had low expression in esophageal squamous cell carcinoma tissues and even lower expression in tumor tissues of metastatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…And overexpression of miR‐515‐5p inhibited the proliferation, invasion, and metastasis of liver cancer cells by regulating the IL‐6/JAK/STAT3 signaling pathway (Ni et al, 2020). However, Yuan indicated that miR‐515‐5p overexpression could inhibit the proliferation and drug resistance of retinoblastoma cells by targeted downregulation of Notch1 expression (Yuan et al, 2020). Moreover, miR‐515‐3p had low expression in esophageal squamous cell carcinoma tissues and even lower expression in tumor tissues of metastatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to circKIF4A, miR-515-5p expressions were markedly decreased in OS, further verifying the combination of the two. miR-515-5p inhibits various cancer processes, for instance, it acts as a prostate cancer inhibitor by targeting TRIP13 [25], suppresses HCC migration as well as invasion via the IL6/JAK/STAT3 pathway [26], inhibits breast cancer cell proliferation, migration as well as invasion via the hsa_circ_0008039/miR-515-5p/CBX4 axis [27]. The functions of miR-515-5p in OS is basically the same as the above researches.…”
Section: Discussionmentioning
confidence: 89%
“…HOTAIR propels carcinogenesis and shows an association with tumor initiation and progression, drug resistance, and poor survival rates of patients [ 28 ]. In previous studies concerning RB, most researchers have selected ARPE-19 cells as the control group [ 29 31 ]. The results of our study found no significant difference in HOTAIR expression between the two normal retinal cell lines ARPE-19 and RPE-1, and thus ARPE-19 cells could be utilized as the ideal control in our experiments.…”
Section: Discussionmentioning
confidence: 99%